2015
DOI: 10.3390/su7079088
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of Convective Heat Transfer Coefficient on External Surfaces of Buildings

Abstract: Convective heat transfer coefficients for external building surfaces are essential in building energy simulation (BES) to calculate convective heat gains and losses from building facades and roofs to the environment. These coefficients are complex functions of: building geometry, building surroundings, local air flow patterns and temperature differences. A microclimatic analysis in a typical urban configuration, has been carried out using Ansys Fluent Version 14.0, an urban street canyon, with a given H/W rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 32 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…A review concluded that the urban microclimate can have a net positive effect on the building energy demand on a yearly basis [15]. Existing studies typically have considered one influential variable isolated from the other influential variables, for example, CHTCs [16][17][18], wind speed [19,20], wind direction [20,21], thermal parameters [22], neighborhood densities [23], urban geometrical parameters [24,25], and solar radiation [26][27][28]. However, there are limited quantitative studies to comprehensively understand understand the impacts of the outdoor built environment on building energy consumption patterns.…”
Section: Introductionmentioning
confidence: 99%
“…A review concluded that the urban microclimate can have a net positive effect on the building energy demand on a yearly basis [15]. Existing studies typically have considered one influential variable isolated from the other influential variables, for example, CHTCs [16][17][18], wind speed [19,20], wind direction [20,21], thermal parameters [22], neighborhood densities [23], urban geometrical parameters [24,25], and solar radiation [26][27][28]. However, there are limited quantitative studies to comprehensively understand understand the impacts of the outdoor built environment on building energy consumption patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The standard k-epsilon (k-e) turbulence model which is frequently used for incompressible flows, was used to define the turbulence kinetic energy and flow dissipation rate within the model [29]. The use of the standard k-e transport model on building configurations has been found accurate in previous works on natural ventilation studies [2][3][4][5][30][31][32][33][34]. The governing equations for the mass conservation, momentum conservation, energy conservation, turbulence kinetic energy and dissipation rate are not included here but fully available in the FLUENT user guide [35].…”
Section: Computational Modellingmentioning
confidence: 99%
“…One important limitation of BES models is their approach to model the convective heat transfer in sheltered building conditions as they do not take into account the influence of neighboring buildings on the local microclimate. The profiles of convective heat transfer coefficient (CHTC) are dynamic and inhomogeneous from a surface to another one throughout the domains; however, this is not considered in BES models (Vollaro et al, 2015; Zhang et al, 2013). Although there were efforts to include CHTC in dynamic CFD-BES coupling studies, most of them were mainly focused on the interior surfaces (Beausoleil-Morrison, 2002; Djunaedy et al, 2003; Negrão, 1998; Zhai and Chen, 2003).…”
Section: Introductionmentioning
confidence: 99%